A Unique Microbial Fingerprint: Isolation And Characterization Of PGPBs Bacteria From Weeds Associated With Cucumber Crop In Iraq (International Journal of Environmental Sciences, 2025)
Plant growth-promoting bacteria as bioioculauts (PGPBs) are abundant around plant roots including some species of Pseudomonas which have an effect on plant growth by stimulating systemic resistance and inhibiting the growth of pathogens. In addition, they protect the plant from environmental and toxic chemical stresses.Therefore, the current study aimed to detect new isolates of PGPBs bacteria colonizing the roots of weeds associated with cucumber crop cultivated in greenhouses. PGPBs samples were collected from the rhizosphere soil of weeds associated with cucumber crop in Diwaniyah province from ten different regions.The results of phenotypic and biochemical diagnosis supported by molecular diagnosis included the registration of three new isolates of Pseudomonas putida, Pseudomonas fluorescens and Pseudomonas chlororaphis, which were deposited in NCBI under the accession numbers (PP582375, PP582376 and PP582377 respectively for the first time in Iraq.